Social Attitudes Towards Historical Films in Contemporary Poland - Białous, Maciej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
Social research indicates that feature films are invariably among the most common sources for acquiring knowledge about the past. Therefore, films are a crucial element of public history and collective memory. However, quantitative social research usually does not focus on how audiences perceive films about history. This article attempts to fill this gap, using the results of a qualitative study involving eight focus group interviews conducted among Polish viewers of historical films. The article answers the questions of how audiences define the historical film genre (paying particular attention to temporal, historical truth and subject criteria), what functions they ascribe to it (educational, emotionalizing, entertaining, political) and what relevance contemporary viewing practices (such as fragmentation of viewing practices, popular interest in series) have for public history and collective memory.